Pengaruh Iklim Organisasi, Pengembangan Karir, dan Stress Kerja Terhadap Kinerja Guru di SD MI Plus El-Hurriyah, Bekasi - Hesty Febriani; Muhammad Wadud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine whether Organizational Climate, Career Development and Work Stress have an effect on Teacher Performance. This study was conducted at SD MI Plus El-Hurriyah, Bekasi. The research method used in this study is a quantitative method. The population in this study were all teachers at the Nurul Ilmi Banyuasin Integrated Education Institution, while the number of samples used was 102 respondents using saturated sampling techniques. The instrument in this study used a questionnaire. The data analysis method in this study used descriptive statistical tests, instrument quality tests, classical assumption tests, multiple regression analysis and hypothesis tests. Based on the results of this study, it is known that the variables of organizational climate, career development and work stress have a significant effect on teacher performance at SD MI Plus El-Hurriyah, Bekasi. with a calculated F value of 32.079 while the F table value is 4.368 thus the calculated F 32.079> F table 4.368. The results of the Determination Test show that the R-Square value is 0.480 or 48.0%, this indicates that the variables of Organizational Climate, Career Development and Work Stress are able to influence Teacher Performance by 52.0%, the remaining 100% - 48.0% = 52% is explained by other variables or factors that are not studied. In a good and optimal organizational climate, career development and work stress will have a good impact on teachers in carrying out their duties and responsibilities so that it will have a positive impact on improving teacher performance and the quality of student learning.